US a narrative history a narrative history a narrative history Vol. 1 Vol. 1 to 1877 to 1877 - Davidson, James West. (New York McGraw-Hill, 2009)
The first civilizations of North America; Old worlds, new worlds [1400-1600]; Colonization and conflict in the South [1600-1750]; Colonization and conflict in the North [1600-1700]; The Mosaic of eighteeth-century America [1689-1771]...
Includes bibliographical references and index.
Includes bibliographical references and index.
Includes bibliographical references and index.
Keywords: United States -- Textbooks -- Textbooks -- Textbooks -- History; Hoa Kỳ (Nước Mỹ); Lịch sử nước Mĩ